PREVALENCE OF MUSCULOSKELETAL DISCOMFORTS AMONG RURAL FARMERS IN NORTH-WESTERN NIGERIA - Abubakar, Maji I.; Abubakar, M. S.; Alhaji, Yusuf (FUDMA JOURNAL OF SCIENCES, 2023)
Agricultural tasks can be considered some of the most demanding and hazardous, especially in developing countries where crop production relies heavily on manual implements. Weeding, one of the common agricultural activities performed by farmers, requires a significant amount of physical effort and often involves awkward wrist and trunk postures, subjecting farmers to multiple risk factors that can result in musculoskeletal discomfort. In this study, a combination of qualitative and quantitative approaches is used to examine the prevalence of musculoskeletal conditions among rural peasant farmers in Jigawa, a state in northwestern Nigeria. The results of this study indicate that lower back pain, upper back pain, and wrist/hand pain are the most prevalent musculoskeletal conditions experienced by peasant farmers who are exposed to intensive manual farming operations.